Leniency bias in subjective performance evaluation : contextual uncertainty and prior employee performance - Gong, Na (2021)
This study examines the influence of contextual uncertainty on leniency biases exhibited in supervisors’ ratings of employees. We conduct a field study examining the performance evaluation of employees in two organizations in China over a four-year period. We focused on two key contextual factors that affect supervisors’ uncertainty in evaluating employees’ performance: supervisors’ span of control and employees’ job non-routineness. Our results show that different forms of uncertainty (supervisor span of control vs. job non-routineness) influence leniency bias, and they moderate prior employee performance on leniency bias in different ways. The study of leniency bias over a longitudinal period in two separate organizations provides a rare opportunity for examining the effect of context on leniency bias, compared to current studies on leniency bias, which tend to focus on lab settings or a single organization.